2020
DOI: 10.1111/jpm.12696
|View full text |Cite
|
Sign up to set email alerts
|

The experience of psychosis and recovery from consumers' perspectives: An integrative literature review

Abstract: Accessible summary What is known on the subject? Since the first decade of this century, few qualitative studies and literature reviews have reported consumers' experiences of psychosis and recovery. The findings from these studies need further exploration. What does the paper add to existing knowledge? New insights into consumers' experiences of psychosis were generated. Additionally, understanding of consumers' conceptions and experiences of recovery were reported. Consumers' insights into the enablers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
0
7
0
8
Order By: Relevance
“…17,[24][25][26][27] Previous studies have shown that community psychiatric nurses play a crucial role in managing people who receive involuntary treatments. 30 Some patients may still have some disease symptoms, so they may lack self-confidence and experience social isolation or even stigmatization, 31 which may hinder their recovery and increase their difficulty in staying in the community. In Chien et al, community psychiatric nurses established relationships with their patients with a nonjudgmental attitude, 24 to allow the patients to engage in the three processes involved in MI: focusing, evoking, and planning.…”
Section: Discussionmentioning
confidence: 99%
“…17,[24][25][26][27] Previous studies have shown that community psychiatric nurses play a crucial role in managing people who receive involuntary treatments. 30 Some patients may still have some disease symptoms, so they may lack self-confidence and experience social isolation or even stigmatization, 31 which may hinder their recovery and increase their difficulty in staying in the community. In Chien et al, community psychiatric nurses established relationships with their patients with a nonjudgmental attitude, 24 to allow the patients to engage in the three processes involved in MI: focusing, evoking, and planning.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a distinction is made between clinical recovery and personal recovery [ 83 ]. This grounding of recovery on the personal perspectives of people who are experts-by-experience is considered fundamental if advances in understanding recovery processes and mechanisms are to be made in ways that make a meaningful difference to experts-by-experience, scientists, clinicians and policy makers [ 93 , 94 , 95 , 96 , 97 ].…”
Section: Mechanistic Approaches To Understanding Psychological Resili...mentioning
confidence: 99%
“…Personal recovery embraces and explores experiences of personal growth as a result of coming through, or better still, being able to simply ‘be with’ severe mental health problems [ 68 , 95 , 96 , 97 , 98 ]. There are extensive evidence-based examples of personal recovery in people with psychosis [ 82 , 83 , 88 ].…”
Section: Mechanistic Approaches To Understanding Psychological Resili...mentioning
confidence: 99%
See 1 more Smart Citation
“…As the family systems theory suggests, individuals cannot be understood in isolation from one another, and any change in one individual within a family is likely to influence the entire system (Kerr & Bowen, 1988). Trustworthy and secure bonds are essential in the recovery process of people who suffer from mental health problems (Alyahya et al, 2020). Family relationships are often problematic and generate mental suffering (Buckmaster et al, 2020).…”
Section: Introductionmentioning
confidence: 99%